The Transcription Factor Pou3f1 Sheds Light on the Development and Molecular Diversity of Glutamatergic Cerebellar Nuclear Neurons in the Mouse - Wu, Joshua Po Han; Yeung, Joanna; Rahimi-Balaei, Maryam; Wu, Sih-Rong; Zoghbi, Huda; Goldowitz, Dan (Frontiers in Molecular Neuroscience, 2022)
The cerebellar nuclear (CN) neurons are a molecularly heterogeneous population whose specification into the different cerebellar nuclei is defined by the expression of varying sets of transcription factors. Here, we present a novel molecular marker, Pou3f1, that delineates specific sets of glutamatergic CN neurons. The glutamatergic identity of Pou3f1+ cells was confirmed by 1) the co-expression of vGluT2, a cell marker of glutamatergic neurons, 2) the co-expression of Atoh1, the master regulator required for the production of all cerebellar glutamatergic lineages, and 3) the absence of Pou3f1-expressing cells in the Atoh1-null cerebellum. Furthermore, the lack of Pax6 and Tbr1 expression in Pou3f1+ cells reveals that Pou3f1-expressing CN neurons specifically settle in the interposed and dentate nuclei. In addition, the Pou3f1-labeled glutamatergic CN neurons can be further classified by the expression of Brn2 and Irx3. The results of the present study align with previous findings highlighting that the survival of the interposed and dentate CN neurons is largely independent of Pax6. More importantly, the present study extends the field’s collective knowledge of the molecular diversity of cerebellar nuclei.